Religioisity in Animated Videos (Quantitative Content Analysis of the Upin and Ipin Animated Show) - Monika Pretty Aprilia; Rivga Agusta; Arselly Dwi Cahyani (Institut Seni Indonesia Yogyakarta, 2022)
The animated children show Upin & Ipin is a popular show in Indonesia that contains many messages that can be a learned by Indonesian children. One of the issues most often carried in the Upin and Ipin show is religiosity, which is raised through worship activities, celebrations of religious holidays, and running daily life in accordance with the teachings of Islam. This study sees the concept of Glock and Stark's religious religion which is divided into five dimensions. The five dimensions are ritual dimension, intellectual dimension, ideology dimension, experimental dimension, and consequence dimension. The method used is quantitative content analysis. The results showed that the ritual dimensions that appeared were the biggest, then the intellectual dimensions and consequence dimensions were also emerged in a smaller percentage. In the animation